(untitled) (International journal of artificial intelligence, 2024)
This article presents a system of exercises designed to enhance oral speech skills in language learners at the C1 level. The system addresses fluency, accuracy, discourse competence, and feedback mechanisms, utilizing a blend of traditional and technology-aided approaches. The article discusses the theoretical framework and practical implementation of the system, highlighting the importance of learner-centered pedagogy and individualized instruction.